2016
DOI: 10.1038/ncomms11659
|View full text |Cite
|
Sign up to set email alerts
|

The machinery underlying malaria parasite virulence is conserved between rodent and human malaria parasites

Abstract: Sequestration of red blood cells infected with the human malaria parasite Plasmodium falciparum in organs such as the brain is considered important for pathogenicity. A similar phenomenon has been observed in mouse models of malaria, using the rodent parasite Plasmodium berghei, but it is unclear whether the P. falciparum proteins known to be involved in this process are conserved in the rodent parasite. Here we identify the P. berghei orthologues of two such key factors of P. falciparum, SBP1 and MAHRP1. Red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 65 publications
(109 reference statements)
6
86
0
Order By: Relevance
“…However, recent studies have shown that P. berghei -infected RBCs can sequester in different organs, including the brain5354, and that accumulation of parasitized RBCs, in addition to the recruitment and sequestration of activated CD8 + T cells55, is necessary for the development of cerebral malaria in mice56. Moreover, there is evidence of an evolutionary conserved machinery underlying sequestration and protein export to the host cell surface between P. berghei and P. falciparum species, although P. berghei lacks PfEMP1 adhesin orthologues57. Taking these findings into consideration, we explain the reduced brain damage in menadione-treated mice in light of our findings that menadione creates an oxidative imbalance in parasitized RBCs that interferes with the export and surface presentation of parasite-encoded virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that P. berghei -infected RBCs can sequester in different organs, including the brain5354, and that accumulation of parasitized RBCs, in addition to the recruitment and sequestration of activated CD8 + T cells55, is necessary for the development of cerebral malaria in mice56. Moreover, there is evidence of an evolutionary conserved machinery underlying sequestration and protein export to the host cell surface between P. berghei and P. falciparum species, although P. berghei lacks PfEMP1 adhesin orthologues57. Taking these findings into consideration, we explain the reduced brain damage in menadione-treated mice in light of our findings that menadione creates an oxidative imbalance in parasitized RBCs that interferes with the export and surface presentation of parasite-encoded virulence factors.…”
Section: Discussionmentioning
confidence: 99%
“…Intravital microscopy (IVM) is a powerful technique to investigate dynamic cellular processes and host-parasite interactions within functioning organs. Organs studied by IVM in the context of parasitology include the brain [1][2][3][4], the skin [5][6][7], the placenta [8,9], the lungs [10], the liver [11][12][13], and the spleen [14,15] (summarized in table 2, green=IVM exists; yellow=organ relevant but IVM never done; grey = IVM not done). Important advances in parasitology have been achieved using wide-field epifluorescence, confocal, spinning disc, or two-photon IVM.…”
Section: Advanced Fluorescence Methods Applied To Intravital Microscopymentioning
confidence: 99%
“…(Image reproduced from Frevert, Nacer, Cabrera, Movila, & Leberl, ) (Scale bar, 50 ÎŒm). (ii) IVM still images showing the lungs of a UBC‐GFP mouse infected with WT PbANKA mCherry parasites displaying sequestration, and the lungs of a UBC‐GFP mouse infected with PbSBP1KO mCherry parasites (absent from the vasculature) (Image reproduced from De Niz et al, ) (Scale bar, 10 ÎŒm). (iii) An important biological finding in the field of Plasmodium was the egress of merozoites from liver‐derived merosomes in the pulmonary capillaries.…”
Section: Organs In the Thoracic Cavitymentioning
confidence: 99%
“…(Figure d(i)). A study using lung IVM in the context of Plasmodium aimed to study the dynamics of P. berghei relative to the vasculature when the machinery for protein export was intact, as opposed to when proteins PbMAHRP1a and PbSBP1 were absent (De Niz et al, ). P. falciparum MAHRP1 and SBP1 are known to be essential for virulence factor export and sequestration.…”
Section: Organs In the Thoracic Cavitymentioning
confidence: 99%